Influence of high-power-low-frequency ultrasonic vibration time on the microstructure and mechanical properties of lead-free solder joints - Tan, A.T.; Tan, A.W.; Yusof, F. (Elsevier, 2016)
Cu/SAC305/Cu solder joints were fabricated at ambient atmosphere using high-power-low-frequency ultrasonic vibration (USV) assisted hot plate reflow soldering. The influences of USV time (within 6 s) on the microstructure, hardness, yield strength and shear strength of the solder joints were investigated. Refinement on the solder matrix microstructure, formation of thinner interfacial Cu6Sn5 IMC layer, and enhancement on the hardness, yield strength and shear strength were observed in all the ultrasonic-treated solder joints. Marked morphological change on the β-Sn phase was observed in the joint solder matrix when the USV time was increased from 1 s to 6 s. Thicker interfacial Cu6Sn5 IMC layer was observed at the top and bottom substrate/solder interfaces and the difference in thickness between these interfaces was greater at increased USV time. The solder matrix hardness increased with increasing USV time, indicating a reduction in joint ductility. The USV time has no influence on the joint shear strength, but decreased joint yield strength was observed after 1 s of USV time. The influences of the USV time on the solder joint properties were contributed by the combined effects of acoustic cavitation and streaming induced by the USV in the molten solder during reflow soldering.